Obesity and dental caries among South Brazilian schoolchildren: a 2.5-year longitudinal study - Nicássia Cioquetta LOCK; Cristiano SUSIN; Carolina Doege BRUSIUS; Marisa MALTZ; Luana Severo ALVES
Abstract The aim of this study was to assess the association between weight status and ΔDMFS among 12-year-old schoolchildren from South Brazil. A total of 801 12-year-old schoolchildren were followed-up for 2.5 ± 0.3 years. Data collection included questionnaire, recording of anthropometric measures (height and weight), and caries examination. The outcome was the difference between DMFS (number of decayed, missing or filled surfaces) at follow-up and baseline (ΔDMFS). Weight status, based on body mass index-for-age Z-scores, was considered the main predictor variable. Negative binomial regression models were used to model the association, and rate ratios and their 95% confidence intervals were estimated. A multivariable fractional polynomial model was used to further explore the relationship between obesity and dental caries. DMFS increased by 0.86 (95%CI = 0.65-1.07), 0.91 (95%CI = 0.59-1.23), and 0.42 (95%CI = 0.03-0.80) for normal weight, overweight, and obese schoolchildren, respectively. Obese adolescents had significantly lower ΔDMFS than normal weight ones (p < 0.05). No significant association between categories of weight status and ΔDMFS was found (overweight, IRR=0.92, 95%CI = 0.69-1.21, p = 0.54; obese IRR = 0.75, 95%CI = 0.51-1.12, p = 0.16). However, the multivariable fractional polynomial model showed an inverted U shaped relationship with a decreasing ΔDMFS with increasing BMI (p < 0.05). This population-based longitudinal study showed an inverse association between obesity and ΔDMFS over a 2.5-year period among South Brazilian adolescents.